2017
DOI: 10.1159/000481684
|View full text |Cite
|
Sign up to set email alerts
|

MMP-9 and Its Regulators TIMP-1 and EMMPRIN in Patients with Acute ST-Elevation Myocardial Infarction: A NORDISTEMI Substudy

Abstract: Objectives: The extracellular matrix is involved in wound repair after acute myocardial infarction (AMI). We investigated whether matrix metalloproteinase (MMP)-9, tissue inhibitor of metalloproteinases (TIMP)-1, and the MMP inducer (EMMPRIN) are associated with infarct size, left ventricular function, and clinical outcome in ST-elevation-MI (STEMI). Methods: In 243 STEMI patients, circulating EMMPRIN, MMP-9, and TIMP-1 were analyzed 3 days and 3 months post-AMI. Infarct size and left ventricular ejection frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 28 publications
3
19
0
1
Order By: Relevance
“…Higher circulating MMP-9 and TIMP-1 levels and MMP-9/TIMP-1 ratios were reported in ischemic cardiomyopathy [36] and are associated with disease severity in heart failure [37] and tissue remodeling in myocardial hypertrophy [38]. The TIMP-1 was further shown to correlate with infarct size in ST-elevation myocardial infarction [39]. Both MMP-2 and MMP-9 are involved in several cardiovascular and inflammatory diseases; they have been previously associated with critical disease progression and organ injury; however, their predictive value in a heterogeneous group of critically ill patients has not yet been evaluated.…”
Section: Mmps and Timps In Critical Illness And Cardiovascular Diseasementioning
confidence: 99%
“…Higher circulating MMP-9 and TIMP-1 levels and MMP-9/TIMP-1 ratios were reported in ischemic cardiomyopathy [36] and are associated with disease severity in heart failure [37] and tissue remodeling in myocardial hypertrophy [38]. The TIMP-1 was further shown to correlate with infarct size in ST-elevation myocardial infarction [39]. Both MMP-2 and MMP-9 are involved in several cardiovascular and inflammatory diseases; they have been previously associated with critical disease progression and organ injury; however, their predictive value in a heterogeneous group of critically ill patients has not yet been evaluated.…”
Section: Mmps and Timps In Critical Illness And Cardiovascular Diseasementioning
confidence: 99%
“…Clinical research showed that serum MMP-9 levels could be an early marker of plaque rupture contributing to acute coronary syndrome [25]. e pathological plaque rupture process that involves inflammation and fibrosis in AS could Evidence-Based Complementary and Alternative Medicine be regulated by MMP-9 and TIMP-1 [26]. In the present study, the expression of MMP-9 and TIMP-1 was regulated by PNS, illuminating plaque vulnerability to its products.…”
Section: Discussionmentioning
confidence: 48%
“…MMP-9 являются желатиназой, которая может деградировать желатины, коллагены и различные компоненты миокарда [14,15]. К тому же MMP-9 способна локализоваться внутри кардиомиоцитов и непосредственно повреждать сократительный аппарат путем расщепления миозина [16,17].…”
Section: Discussionunclassified